BANTUAN PERENCANAAN DINDING PENAHAN TANAH KELURAHAN SAMBIROTO, KECAMATAN TEMBALANG, KOTA SEMARANG - Shifa Fauziyah; Moh Nur Sholeh; Fardzanela Suwarto (Sekolah Vokasi Universitas Diponegoro, 2021)
Landslide risk is common on most slopes. It happened suddenly. Landslides are caused by the presence of shear stress and a decrease in shear strength in the landslide area. Sambiroto Urban Village is one of the areas with relatively steep slopes so that it is prone to landslides. One method to overcome landslides is to install a retaining wall. The design of a secure retaining wall must take into account the factors of safety for shear, overturning and bearing capacity. Based on the calculation of retaining wall designed is gravity type with height 500 cm, width under 280 cm, width 55 cm, with retaining wall soil entering ground as high as 70 cm. Gravity retaining walls with these dimensions have been analyzed to be safe against overturning hazards, shear hazards and bearing capacity.